Research Progress of Biomarkers for Sepsis and Precision Medicine - Neng Wang; Hansheng Huang; Youlin Tan; Nai Zhang (Emergency Medicine International)
Since 1989, the definition of sepsis has been revised several times. The 2016 Sepsis-3 consensus definition of sepsis aims to improve diagnostic accuracy and reduce the frequency of misdiagnosis. The Sequential Organ Failure Assessment (SOFA) scoring system facilitates personalized treatment. Sepsis-related biomarkers are essential for diagnosis, treatment, and prognosis; however, their widespread application is limited by their insufficient sensitivity and specificity. From October 2019 to October 2024, 4801 studies had reported on sepsis-related biomarkers. The number of studies initially increased but subsequently decreased over time (beginning from 2021). C-reactive protein (CRP) and procalcitonin (PCT) are the most frequently investigated biomarkers, and their combination with other biomarkers can improve diagnostic accuracy. Advancements in data-driven technologies have helped optimize the definition of sepsis, accelerate early diagnosis, clarify subphenotypes, improve prognostic assessment, and develop personalized treatment strategies. With the deepening of research on the pathological mechanisms of sepsis, novel biomarkers such as vascular endothelin, vasoactive peptides, BMP9, cytokines, chemokines, and cfDNA have emerged, which are closely related to the severity of the disease. The clinical application of known biomarkers has expanded, and their kinetic changes are considered more accurate than a single value in predicting outcomes. In addition, related studies have focused on the exploration of precision medicine for sepsis. Efforts have been made to divide patients into more homogeneous subgroups by distinguishing their shared biological characteristics, thus providing valuable avenues for developing novel therapeutic approaches. This article reviews the research status of some commonly used sepsis biomarkers from October 2019 to October 2024, analyzes the current application status and limitations, pays attention to the changes of biomarkers and the exploration of precision medicine for sepsis, and aims to develop new treatment approaches by dividing patients into subgroups.